Roxburghine B and OxoxylopinePotential as Hepcidin Antagonist Insilico for Inflammatory Anemia - Safirah . Yotriana; Yuliana Heri Suselo; Muthmainah . . (Nexus Biomedika, 2017)
Introduction: Anemia affects half a billion women in the world and become a problem, especially in pregnant women. One of the cause of anemia is inflammatory disease which also has a high prevalence in Indonesia. Therapies currently used to treat anemia are based on the underlying disease. Anticalin is a protein that works as hepcidin antagonist. Anticalin has completed the clinical phase II, but it has not been distributed to public market yet. Therefore, a new, easily accessible and more effective drug is required. Indonesian herbs have been widely used as medicinal plants in the community and are potential to be developed as drugs. The purpose of this study is to identify Indonesian phytochemicals that can act as hepcidin antagonist. Methods: The research was a bioinformatics study with molecular docking method. Three-dimensional structure of human hepcidin as a target protein and Anticalinas a standar therapy were downloaded from the website of the Protein Data Bank (PDB). The active compounds were obtained from HerbalDB and the three-dimensional structure was from PubChem National Center for Biotechnology Information (NCBI). This study was performing using AutoDock Vina 1.1.2 to analyze the binding affinity. Molecular modification was performed with Autodock Tools 1.5.6. Visualization was done with Chimera 1.10 and PyMol 1.3. Results: The docking scores between hepcidin and Anticalin was -4.6 kcal/mol at Cys13,Cys14, Arg16, and Ser17. The compound Roxburghine B and Oxoxylopine could interact with the ligand binding domain and had the docking scores lower than Anticalin. Conclusions: Roxburghine B and Oxoxylopine are potential to become hepcidin antagonists insilico for inflammatory anemia. Keywords: anemia inflamasi, phytochemical, molecular docking, hepcidin, Anticalin